2012
DOI: 10.1111/ijpp.12009
|View full text |Cite
|
Sign up to set email alerts
|

Implementation of clinical pharmacy services at a university hospital in Jordan

Abstract: The implementation of clinical pharmacy services in this setting was successful and should positively impact patient care.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
15
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 18 publications
(17 citation statements)
references
References 10 publications
(26 reference statements)
1
15
1
Order By: Relevance
“…Twelve studies evaluated process outcomes, TRPs, and pharmacist interventions. 9 , 13 , 14 , 17 , 18 , 20 , 32 , 34 , 35 , 37 - 39 Therapeutic outcomes were reported in 9 studies. 10 , 20 , 23 , 30 - 35 Eleven studies reported humanistic outcomes.…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…Twelve studies evaluated process outcomes, TRPs, and pharmacist interventions. 9 , 13 , 14 , 17 , 18 , 20 , 32 , 34 , 35 , 37 - 39 Therapeutic outcomes were reported in 9 studies. 10 , 20 , 23 , 30 - 35 Eleven studies reported humanistic outcomes.…”
Section: Resultsmentioning
confidence: 99%
“…Most studies were of moderate quality 9 , 11 , 12 , 14 , 17 , 20 , 23 , 31 , 32 , 34 , 36 and 3 were scored at high quality. 10 , 24 , 37 Studies often showed methodological strength with respect to standardized delivery of the intervention and outcome measurement.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations